Cell damage shifts the microRNA content of small extracellular vesicles into a Toll-like receptor 7-activating cargo capable to propagate inflammation and immunity - Valentina Salvi; Carolina Gaudenzi; Barbara Mariotti; Gaia Giongrandi; Silvia Alacqua; Veronica Gianello; Tiziana Schioppa; Laura Tiberio; Angela Ceribelli; Carlo Selmi; Paolo Bergese; Stefano Calza; et al. (Cell Communication and Signaling)
Abstract Background The physiological relevance of cell-to-cell communication mediated by small extracellular vesicle-encapsulated microRNAs (sEV-miRNAs) remains debated because of the limiting representativity of specific miRNAs within the extracellular pool. We hypothesize that sEV-miRNA non-canonical function consisting of the stimulation of Toll-like receptor 7 (TLR7) may rely on a global shift of the sEV cargo rather than on the induction of one or few specific miRNAs. Psoriasis represents an ideal model to test such hypothesis as it is driven by overt activation of TLR7-expressing plasmacytoid dendritic cells (pDCs) following keratinocyte damage. Methods To mimic the onset of psoriasis, keratinocytes were treated with a cocktail of psoriatic cytokines or UV-irradiated. SmallRNA sequencing was performed on sEVs released by healthy and UV-treated keratinocytes. sEV-miRNAs were analyzed for nucleotide composition as well as for the presence of putative TLR7-binding triplets. Primary human pDCs where stimulated with sEVs +/- inhibitors of TLR7 (Enpatoran), of sEV release (GW4869 + manumycin) and of TLR7-mediated pDC activation (anti-BDCA-2 antibody). Secretion of type I IFNs and activation of CD8+T cells were used as readouts. qPCR on psoriatic and healthy skin biopsies was conducted to identify induced miRNAs. Results sEV-miRNAs released by damaged keratinocytes revealed a significantly higher content of TLR7-activating sequences than healthy cells. As expected, differential expression analysis confirmed the presence of miRNAs upregulated in psoriatic skin, including miR203a. More importantly, 76.5% of induced miRNAs possessed TLR7-binding features and among these we could detect several previously demonstrated TLR7 ligands. In accordance with this in silico analysis, sEVs from damaged keratinocytes recapitulated key events of psoriatic pathogenesis by triggering pDCs to release type I interferon and activate cytotoxic CD8+T cells in a TLR7- and sEV-dependent manner. Discussion Our results demonstrate that miR203a is just one paradigmatic TLR7-activating miRNA among the hundreds released by UV-irradiated keratinocytes, which altogether trigger pDC activation in psoriatic conditions. This represents the first evidence that cell damage shifts the miRNA content of sEVs towards a TLR7-activating cargo capable to propagate inflammation and immunity, offering strong support to the physiological role of systemic miRNA-based cell-to-cell communication.